Using social exchange theory to understand non-terminal palliative care referral practices for Parkinson's disease patients. (October 2017) - Prizer, Lindsay P; Gay, Jennifer L; Perkins, Molly M; Wilson, Mark G; Emerson, Kerstin G; Glass, Anne P; Miyasaki, Janis M
Background: A palliative approach is recommended in the care of Parkinson's disease patients; however, many patients only receive this care in the form of hospice at the end of life. Physician attitudes about palliative care have been shown to influence referrals for patients with chronic disease, and negative physician perceptions may affect early palliative referrals for Parkinson's disease patients. Aim: To use Social Exchange Theory to examine the association between neurologist-perceived costs and benefits of palliative care referral for Parkinson's disease patients and their reported referral practices. Design: A cross-sectional survey study of neurologists. Setting/participants: A total of 62 neurologists recruited from the National Parkinson Foundation, the Medical Association of Georgia, and the American Academy of Neurology's clinician database. Results: Participants reported significantly stronger endorsement of the rewards ( M = 3.34, SD = 0.37) of palliative care referrals than the costs ( M = 2.13, SD = 0.30; t (61) = −16.10, p < 0.0001). A Poisson regression found that perceived costs, perceived rewards, physician type, and the number of complementary clinicians in practice were significant predictors of palliative care referral. Conclusion: Physicians may be more likely to refer patients to non-terminal palliative care if (1) they work in interdisciplinary settings and/or (2) previous personal or patient experience with palliative care was positive. They may be less likely to refer if (1) they fear a loss of autonomy in patient care, (2) they are unaware of available programs, and/or (3) they believe they address palliative needs. Initiatives to educate neurologists on the benefits and availability of non-terminal palliative services could improve patient access to this care.